REDESAIN TENGARAN KECAMATAN BLAHBATUH GIANYAR - LESTARI, AYU PUTU UTARI PARTHAMI; MARDANA, I KADEK YUDI (Universitas Mahasaraswati K. Mataram, 2024)
In general, landmarks are unique physical forms that can be used as a guide for users of an area to facilitate orientation and also help develop the character of an area. This goal can be realized more easily if the physical (architectural) elements also reflect the local cultural values of the area. Landmarks are a crucial aspect of the city structure as they help individuals orient themselves and understand the city as a whole from a particular point. Landmarks can be various structures such as monuments, statues, buildings, towers, places of worship, and others. The importance of landmarks as reference points for observers to spatial locations has been considered in regional planning, as is the case in Gianyar, Bali. In Blahbatuh District, Gianyar, there is a landmark in the form of Hanoman statue made by KKN students. However, the statue is considered to be made without thinking about the history or characteristics of the village, so there is a need for a redesign design to improve the quality of urban life both in terms of the environment and society. The problems that occur will be observed and then analyzed. The approach applied was a descriptive qualitative one involving theoretical explanations of landmarks as well as direct observation of the objects observed. By analyzing the characteristics of the environment, aesthetic needs, and landmark functions, this research produces design recommendations that also consider aspects of beauty, local identity, and sustainability. The proposed design is a 9m high statue of Dewi Sri, as a reminder that the neighborhood is a rice producer. This design replaces the previous Hanoman Statue which was deemed less reflective of the locality context. The design results are expected to be a reference for the development and revitalization of the area, as well as increasing the attractiveness and uniqueness of local tourist destinations. Hopefully, this research can also play a role in advancing sustainable architecture and design in rural areas